The Effect of Gross Profit Margin (GPM) on Profit Growth at the Indonesian Employee Cooperative (KPRI) Torch of Teachers Bima - Wulan Indah Sari; Puji Muniarty (Yayasan Ilomata, 2021)
Objective research to analyze the influence of GPM to profit growth in (KPRI) The Torch of Bima Teachers. The research cooperative instrument used was a list of tables containing data on gross profit, net sales and net income (KPRI) Torch Guru-Guru Bima. The population in the study used was the financial report data of the Torch Teachers of Bima balance and PHU for the last 49 years, namely the years 1970-2019. The sample used is the financial data of the Bima Teachers Torch Cooperative for 10 years for the period 2010-2019. The research sampling method was purposive sampling method. Data collected through observation, interview and literature. Data analysis techniques used are GPM, Profit Growth, Simple Linear Regression Analysis, Simple Correlation Coefficient Analysis, Simple Coefficient of determination and partially theresults t testshow that there is no significant effect of GPM on profit growth at (KPRI) Torch of Bima.